2023
DOI: 10.3390/plants12040770
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Grassland Ecosystem Structure and Stability and Inspiration for Improving Its Service Capacity in the Karst Desertification Control

Abstract: The structure and stability of grassland ecosystems have a significant impact on biodiversity, material cycling and productivity for ecosystem services. However, the issue of the structure and stability of grassland ecosystems has not been systematically reviewed. Based on the Web of Science (WOS) and China National Knowledge Infrastructure (CNKI) databases, we used the systematic-review method and screened 133 papers to describe and analyze the frontiers of research into the structure and stability of grassla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 214 publications
0
7
0
Order By: Relevance
“…However, a shift occurs in the long term, where resource limitation in highproductivity grasslands results in aggravated interspecific competition. Consequently, slowgrowing and long-lived species with higher competitive advantages suppress or even exclude less competitive species (Borer et The controlled grazing approach has emerged as a significant factor in shaping the composition of plant communities and influencing the distribution of different plant groups and species (He et al, 2023;Smith et al, 2017). The findings of this research underscore the potential of controlled grazing to positively impact vegetation management and conservation efforts, leading to Considering land cover changes, vegetation dynamics, biomass production, and average NDVI values in tandem is of crucial importance when evaluating the impacts of controlled grazing management (Figure 3; Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, a shift occurs in the long term, where resource limitation in highproductivity grasslands results in aggravated interspecific competition. Consequently, slowgrowing and long-lived species with higher competitive advantages suppress or even exclude less competitive species (Borer et The controlled grazing approach has emerged as a significant factor in shaping the composition of plant communities and influencing the distribution of different plant groups and species (He et al, 2023;Smith et al, 2017). The findings of this research underscore the potential of controlled grazing to positively impact vegetation management and conservation efforts, leading to Considering land cover changes, vegetation dynamics, biomass production, and average NDVI values in tandem is of crucial importance when evaluating the impacts of controlled grazing management (Figure 3; Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Intercropping in the agro-grass management model effectively maintains the productivity of (S. miltiorrhiza) as well as improves soil structural stability and water recycling efficiency [30]. Restoration measures, such as mixing legume and grass families, forage and crop rotation, and degraded grassland improvement, are not only beneficial to regional industrial development [64], but also play an important role in optimizing the regional ecosystem services of soil conservation and water harvesting. A variety of ecological restoration optimization composite measures are formed to jointly promote the restoration and development of ecologically fragile areas.…”
Section: Future Responses To Rocky Desertification Control Based On E...mentioning
confidence: 99%
“…Studies have shown that "grain for green" projects in rocky desertification areas are an important measure to restore the ecological environment damaged by rocky desertification, which is of great significance to promote ecological restoration and economic development [23]. The establishment of artificial grassland or natural recovery and secondary succession without human intervention of grassland may change the soil-plant-microorganism nutrient relationship formed by long-term evolution [23,24], thus having a profound impact on the balance of elements and substances in the ecosystem [25,26]. Up to now, research on ecological stoichiometry in karst areas has seen many achievements in vegetation succession, some vegetation (e.g., forest) or areas (e.g., grassland in northern China) [27][28][29][30][31], but research on ecological stoichiometry of the plant-soil-microorganism system in grasslands of the karst desertification control area is still very weak.…”
Section: Introductionmentioning
confidence: 99%